2D Transition‐Metal‐Dichalcogenide‐Nanosheet‐Based Composites for Photocatalytic and Electrocatalytic Hydrogen Evolution Reactions. Issue 10 (16th December 2015) - Lu, Qipeng; Yu, Yifu; Ma, Qinglang; Chen, Bo; Zhang, Hua
Abstract : Hydrogen (H2 ) is one of the most important clean and renewable energy sources for future energy sustainability. Nowadays, photocatalytic and electrocatalytic hydrogen evolution reactions (HERs) from water splitting are considered as two of the most efficient methods to convert sustainable energy to the clean energy carrier, H2 . Catalysts based on transition metal dichalcogenides (TMDs) are recognized as greatly promising substitutes for noble‐metal‐based catalysts for HER. The photocatalytic and electrocatalytic activities of TMD nanosheets for the HER can be further improved after hybridization with many kinds of nanomaterials, such as metals, oxides, sulfides, and carbon materials, through different methods including the in situ reduction method, the hot‐injection method, the heating‐up method, the hydro(solvo)thermal method, chemical vapor deposition (CVD), and thermal annealing. Here, recent progress in photocatalytic and electrocatalytic HERs using 2D TMD‐based composites as catalysts is discussed. Abstract : Transition‐metal dichalcogenide (TMD)‐based catalysts have great promise as substitutes for noble‐metal‐based catalysts for hydrogen‐evolution reactions. Recent strategies regarding the various kinds of TMD‐based composites for photocatalytic and electrocatalytic hydrogen evolution are summarized here. In addition, the challenges and opportunities are provided.